A Systematic Approach for Identifying System Requirements from the Organization’s Business Model - Knight, Debora Mac; Araujo, Renata M.; Borges, Marcos R. S. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2005: Anais do II Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2005.14975, 2005)
Although it is recognized that the business model contains relevant information for obtaining system requirements, we still lack a systematic approach for discovering requirements from an existing organization’s business model. This paper proposes a method which starts from a business model, guides the software development team toward understanding business needs and identifying system requirements addressing those needs. Three case studies were conducted where the method applicability could be verified